New contours of development of higher professional education in the field of physical culture and sports - Lubysheva L.I. ,; Rosenko S.I. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify current trends in the development of theory and practice of personnel training based on modern principles of building a system of professional education in the field of physical culture and sports. Methods and structure of the study. An analysis of information and analytical materials was carried out based on the results of monitoring the activities of educational organizations of higher education in Russian universities of physical culture and sports. Results and conclusions. Currently, higher professional education in the field of physical culture and sports is undergoing transformations determined by the requirements of the modern labor market. The outlined contours of the development of higher education in the field of physical culture and sports are closely related to the formation of multi-stage education (bachelor-master), an increase in the number of student populations, the predominance of public sector students, a reduction in the number of implemented enlarged groups of directions, and the development of the “specialization” of higher sports education. The identified trends determine further ways to improve the theory and practice of industry education aimed at training specialists in the field of physical culture and sports.